Porphyrin nanorods modified glassy carbon electrode for the electrocatalysis of dioxygen, methanol and hydrazine - George, Reama C.; Mugadza, Tawanda; Khene, Samson; Egharevba, Gabriel O.; Nyokong, Tebello (Wiley, 2016)
Porphyrin nanorods (PNR) were prepared by ionic self-assembly of two oppositely charged porphyrin molecules consisting of free base meso-tetraphenylsulfonate porphyrin (H4TPPS42−) and meso-tetra(N-methyl-4-pyridyl) porphyrin (MTMePyP4+M=Sn, Mn, In, Co). These consist of H4TPPS42− SnTMePyP4+, H4TPPS42− CoTMePyP4+, H4TPPS42− InTMePyP4+ and H4TPPS42− MnTMePyP4+ porphyrin nanorods. The absorption spectra and transmission electron microscopic (TEM) images of these structures were obtained. These porphyrin nanostructures were used to modify a glassy carbon electrode for the electrocatalytic reduction of oxygen, and the oxidation of hydrazine and methanol at low pH. The cyclic voltammogram of PNR-modified GCE in pH 2 buffer solution has five irreversible processes, two distinct reduction processes and three oxidation processes. The porphyrin nanorods modified GCE produce good responses especially towards oxygen reduction at −0.50 V vs. Ag|AgCl (3 M KCl). The process of electrocatalytic oxidation of methanol using PNR-modified GCE begins at 0.71 V vs. Ag|AgCl (3 M KCl). The electrochemical oxidation of hydrazine began at around 0.36 V on H4TPPS42− SnTMePyP4+ modified GCE. The GCE modified with H4TPPS42− CoTMePyP4+ H4TPPS42− InTMePyP4+ and H4TPPS42− MnTMePyP4+ porphyrin nanorods began oxidizing hydrazine at 0.54 V, 0.59 V and 0.56 V, respectively.